Strategi Promosi Virtual Tour oleh KEMENPAREKRAF dan Traveloka Melalui Media Sosial Instagram - Natasha Erinda Putri Moniaga; I Made Bayu Ariwangsa; Dian Pramita Sugiarti (JURNAL DESTINASI PARIWISATA, 2022)
Pandemic caused by the Covid-19 virus paralyzed many sectors of activities in the community, including thetourism sector so that a strategy to promote tourism through virtual travel is needed. Traveling is difficultto do because of restrictions on activities carried out by the government, in order to reduce the rate of spreadof this disease. People are forced to be quiet and work indoors, although some types of jobs are still allowedto move. Staying indoors and not being able to travel can certainly cause its own stress. On social media later,one of them, appeared various services that offer virtual tourism services, including those held by theMinistry of Tourism. This service invites participants to travel together through various online media,provided by a guide who will lead the course of the activity, just as is commonly done in the real world. Thispromotional strategy is expected to be able to; 1) increase tourist interest in virtual traveling, 2) the creationof digital tourism for the future, 3) ease of travel, 4) Emphasis on travel costs, 5) the sustainability of virtualtraveling. The purpose of this study was to look at the promotional strategies carried out by Kemenparekrafand Traveloka, as well as review the effectiveness of the virtual travel service. To be able to answer theproblem, quantitative research methods are used by distributing questionnaires to a number of eightystudents. The results of this study can be used to assess the effectiveness of virtual tourism and its possiblefuture development.Keywords : Virtual Travelling, Promotional Strategies, Social Media